ANALISIS PENGARUH TINGKAT KEBUTUHAN DAN BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN DENGAN CITRA MEREK SEBAGAI VARIABEL MEDIASI - Retno Susanti, Dina Oktaviana, Y. Djoko Suseno & (Universitas Slamet Riyadi, 2016)
The purpose of this study was to analyze the effect of: 1) Level of needs on brand image. 2) Marketing mix on brand image. 3) Level of needs on purchase decision. 4) Marketing mix on purchase decision. 5) Brand image on purchase decision. 6) Level of needs on purchase decisions with brand image as a mediating variable and 7) Marketing mix on purchase decisions with brand image as a mediating variable. This study is a survey and types of data are quantitative and qualitative data. The data source used primary dand secondary data. The study population of consumers who purchased a Yamaha motorcycle in Deta Kartasura Dealer. The research sample of 50 people with convenience sampling technique. The technique of collecting data used interviews, observation and questionnaires. Data were analyzed used path analysis. Level of needs has significant effect on brand image. Marketing mix has significant effect on brand image. Level of needs has significant effect on purchase decisions. Marketing mix has significant effect on purchase decisions. Brand image has significant effect on purchae decisions. Level of needs has significant effect on purchase decisions with brand image as a mediating variable. Marketing mix has significant effect on purchase decisions with brand image as a mediating variable.Keywords: level of needs, marketing mix, brand image, purchase decision